2014
DOI: 10.5380/pes.v24i1.39028
|View full text |Cite
|
Sign up to set email alerts
|

Fatores Ambientais Que Afetam a Eficácia De Glifosato: Síntese Do Conhecimento

Abstract: A presente revisão objetivou organizar e sintetizar o conhecimento disponível na literatura com respeito aos fatores ambientais que afetam a efi cácia do glifosato. Foram abordados os seguintes aspectos: temperatura, umidade relativa do ar, solo, irradiância, disponibilidade de nutrientes e o estado nutricional das plantas, ocorrência de chuva após a aplicação do produto, assim como a interação entre o ambiente e as características morfológicas e fenológicas das plantas. Verifi cou-se que, em geral, temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
1
4
0
3
Order By: Relevance
“…In this sustainable context, the lowest dose of glyphosate applied in the morning and afternoon, in both investigated volumes, presented satisfactory results and there was no significant difference for the response variables when compared to the other doses used. Vidal et al (2014) corroborate this idea and claim that simply increasing the dose of herbicides has not been the most appropriate procedure to ensure the effectiveness of control. Rodrigues et al (2018) emphasize that the correct dose in burndown can vary according to the species and stage of development.…”
Section: Resultsmentioning
confidence: 83%
“…In this sustainable context, the lowest dose of glyphosate applied in the morning and afternoon, in both investigated volumes, presented satisfactory results and there was no significant difference for the response variables when compared to the other doses used. Vidal et al (2014) corroborate this idea and claim that simply increasing the dose of herbicides has not been the most appropriate procedure to ensure the effectiveness of control. Rodrigues et al (2018) emphasize that the correct dose in burndown can vary according to the species and stage of development.…”
Section: Resultsmentioning
confidence: 83%
“…A higher reduction in plant fresh mass was observed when the application occurred at 9 am in relation to 1 am. Daytime applications of glyphosate contribute to better herbicide effectiveness, because to photosynthetic activity and amino acid synthesis pathways being in operation due to the presence of light (Santos Jr et al 2013;Sharkhuu et al 2014;Vidal et al 2014). Applications taken between 9 am and 6 pm provide greater glyphosate efficiency (Martinson et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results in various weed species were observed by Zanatta et al (2007) andSilva Jr. et al (2018). The reduction in efficiency occurs due to lower herbicide absorption and translocation due to morphophysiological changes (Vitorino and Martins 2012), such as thickening and composition of epicuticular wax, leaf pilosity, reduced water potential and modification of leaf orientation (Levene and Owen 1995;Vidal et al 2014;Trezzi et al 2020). Different studies have reported that glyphosate is more efficient when applied at 6 am (Mohr et al 2007), and temperatures near to 25 °C (Degreeff et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Para o controle de plantas suscetíveis, destacam-se ainda as diferenças entre as plantas, assim como as condições ambientais no momento da aplicação, por exemplo, devido à sua absorção relativamente lenta, o glyphosate é facilmente influenciado pela ocorrência de chuvas após aplicação (VIDAL et al 2014). Portanto, a dificuldade de controle de plantas do gênero Urochloa pode estar relacionada às características morfológicas, ao estádio de desenvolvimento das plantas durante a aplicação, à grande quantidade de sementes que permanecem no solo formando banco de sementes, além da produção e liberação de compostos alelopáticos por algumas espécies.…”
Section: Resultsunclassified